Salivary Glands, Oral Pathology, and Obesity: Review (International Journal of Food and Nutritional Sciences, 2022)
Consequently, the obesity epidemic has become widespread. The disease affects more and more children and young people, not only adults. Consuming too much food, especially carbohydrates that have undergone extensive processing, is one of the main causes of overweight and obesity. The salivary glands are one of many organs that are altered by obesity, and these changes have an impact on how they function. Researchers are debating the link between obesity and xerostomia, periodontal disease, and tooth decay.More and more academic studies are highlighting how obesity alters the microbiota of the mouth cavity. The morphological and functional changes to the salivary glands are strongly tied to these changes. The opinions that are now held regarding how obesity affects the health of the salivary glands and how changes to their functions affect other tissues in the oral cavity are presented in this article review.